Selamatkan Bumi Melalui Konstruksi Hijau : Perencanaan, Pengadaan, Konstruksi, & Operasi - ERVIANTO, Wulfram I (Andi Offset, 2012)
Selamatkan Bumi Melalui Konstruksi Hijau : Perencanaan, Pengadaan, Konstruksi, & Operasi